Analısıs Deıksıs pada Novel dan Pemanfaatannya dalam Pembelajaran Bahasa Indonesıa dı SMA - Purlilaiceu, Purlilaiceu; Rostika, Rika (Universitas Mathla'ul Anwar Banten, 2022)
This study examines the deixis phenomenon in the novel Si Anak Strong by Tere Liye by using a pragmatic study. One of the reasons the author examines the novel Si Anak Strong as the object of research, is because it has various forms of deixis and has its own characteristics, making it interesting to study. This study uses a qualitative approach with a descriptive method, namely a description of a situation that takes place not only collecting data but also analyzing, interpreting, and concluding. Based on the results and discussion of research that has been carried out on data from sentences in the dialogue of Tere Liye's novel Si Anak Strong containing deixis, it is found that there are forms of person deixis, space/place deixis, and time deixis. In this regard, the researchers used the results of the research as teaching materials for learning Indonesian Language and Literature at the XII grade high school level by referring to the 2013 revised 2017 curriculum syllabus. In addition, the researchers used novels as teaching materials for Indonesian Language and Literature learning in high school from grade level. XII in improving language skills.